Optimizing pharmacotherapy and deprescribing strategies in older adults living with multimorbidity and polypharmacy: EuGMS SIG on pharmacology position paper - Poelgeest, Eveline van; Seppala, Lotta; Bahat, Gulistan; Ilhan, Birkan; Mair, Alpana; van Marum, Rob; Onder, Graziano; Ryg, Jesper; Fernandes, Marília Andreia; Cherubini, Antonio; Denkinger, Michael D.; Eidam, Annette; et al. (European geriatric medicine, 2023)
Aim: To summarize the literature on medication review and deprescribing in older adults, and formulate recommendations to improve prescribing medications in older, multimorbid adults with polypharmacy. Findings: Current evidence demonstrates a need for a multifaceted and wide-scale change in education, guidelines, research, advocacy, and policy to improve the management of polypharmacy in older people, and to make deprescribing part of routine care for the ageing generations to come. Message: By implementing the recommendations in this paper, healthcare professionals will be better prepared to address the challenges associated with an ageing population and provide high-quality care to older patients with complex health and social care needs.